Intervención del terapista respiratorio en paciente masculino de 32 años de edad con diagnostico de neumonía intrahospitalaria asociada a la ventilación mecánica. - Rochina Chiluiza, Melisa Jamileth (2022)
This case study was based on the intervention of the respiratory therapist in a 32-year-old male patient diagnosed with hospital-acquired pneumonia associated with ventilation. Nosocomial pneumonia associated with mechanical ventilation is an infection that develops after patients stay for more than 48 hours in hospitals, it has a high mortality and morbidity rate. This pathology prolongs the stay of patients in the intensive care unit. The main objective of the clinical case is based on knowing the main triggering factors of nosocomial pneumonia associated with mechanical ventilation and, in turn, knowing the prevention measures that must be carried out in all patients who are admitted to the intensive care unit. The main signs and symptoms presented by patients with hospital-acquired pneumonia associated with mechanical ventilation are loss of appetite, unquantified thermal rise accompanied by chills, general malaise, nausea accompanied by vomiting, respiratory distress, cough with sputum, headache, pain at the level of the chest, weight loss.